How do horizontal, frictional discontinuities affect reverse fault-propagation folding?. (September 2017) - Bonanno, Emanuele; Bonini, Lorenzo; Basili, Roberto; Toscani, Giovanni; Seno, Silvio
Abstract: The development of new reverse faults and related folds is strongly controlled by the mechanical characteristics of the host rocks. In this study we analyze the impact of a specific kind of anisotropy, i.e. thin mechanical and frictional discontinuities, in affecting the development of reverse faults and of the associated folds using physical scaled models. We perform analog modeling introducing one or two initially horizontal, thin discontinuities above an initially blind fault dipping at 30° in one case, and 45° in another, and then compare the results with those obtained from a fully isotropic model. The experimental results show that the occurrence of thin discontinuities affects both the development and the propagation of new faults and the shape of the associated folds. New faults 1) accelerate or decelerate their propagation depending on the location of the tips with respect to the discontinuities, 2) cross the discontinuities at a characteristic angle (∼90°), and 3) produce folds with different shapes, resulting not only from the dip of the new faults but also from their non-linear propagation history. Our results may have direct impact on future kinematic models, especially those aimed to reconstruct the tectonic history of faults that developed in layered rocks or in regions affected by pre-existing faults. Highlights: We focus on the role of thin frictional discontinuities in affecting the development of reverse faults. Our method is based on wet clay analog models. Our study show the impact of discontinuities on both propagation rate of faults and on development of the associated folds.